Pioneer women in engineering studies: what can we learn from their experiences?. (1st November 2016) - Pardo, P.; Calvet, M.D.; Pons, O.; Martinez, M.C.
ABSTRACT: Women's access to higher education in Spain began in the last third of the nineteenth century. However, the full incorporation of women into technical studies did not occur until a century later. This article presents the results of research into the access of the first women to do technical studies in Catalonia (northeast Spain). Data have been collected from 11 technical schools belonging to the Universitat Politècnica de Catalunya (UPC) with the aim of understanding the dynamics of the incorporation of women into these schools between 1851 (foundation of the first engineering school in Catalonia) and 1980. Interviews were conducted with 21 pioneer women who completed their technical studies. Their experiences show how technical schools had to adapt, both physically and culturally, to female students. Finally, the current status of female engineers in Catalonia is compared with the situation in other Western countries. Similarities are found that show the relevance of gender as a social structuring force.